Whistleblowing dan Niat Melaksanakannya Mahasiswa - Fathiyah Fathiyah; Mufidah Mufidah; Masnun Masnun (Ekonomis: Journal of Economics and Business, 2019)
Being a whistleblower is not an easy matter. Someone from internal organizations will face an ethical dilemma in deciding whether to "blow the whistle" or leave it hidden. Some view whistleblowers as traitors who violate the norms of organizational loyalty, others see whistleblowers as heroic protectors of truth values, not just loyalty to conflicting organizations, causing potential whistleblowers to experience a dilemma in determining attitudes that can distort Whistleblowing interests..This research examines and analyzes the effect seriousness of the violation, organizational commitment, academic potential and gender towards possible intentions to Whistleblowing by students. Therefore this study would like to apply the Theory of Planned Behavior concept which explains that the behavior carried out by individuals arises because of the intention that underlies the behavior .Data analysis uses logistic regression analysis with SPSS 22.00 for Windows. The result indicates that Gender and  organizational commitment have significant impact on probability of intention to do Whistleblowing.